2000
DOI: 10.1054/bjoc.1999.1082
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in post-menopausal plasma oestrogen levels: high oestrone levels in Japanese-American women despite low weight

Abstract: Until recently women in Japan were at very low risk of breast cancer (Ursin et al, 1994), particularly in the post-menopausal period when age-specific breast cancer rates remained essentially constant in contrast to the rates in the USA which continue to steadily increase in the post-menopausal period . Studies of plasma oestrogen concentrations in 'traditional' Asians (living in Asia) compared with Whites have found lower concentrations in the Asians (Goldin et al, 1986;Key et al, 1990;Shimizu et al, 1990). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 23 publications
3
36
0
Order By: Relevance
“…More specifically, Asian women have a three-fold lower breast cancer risk than women in the United States, independent of body weight [33]. However, second and third generation descendants of women who migrated from Asia to Western countries have breast cancer risks similar to those of women in the host country, suggesting that lifestyle and dietary habits, and not genetic factors explain the low breast cancer risk of women in Asia [30,34,35]. Furthermore, epidemiologic studies have detected an association between phytoestrogen consumption, phytoestrogen levels in plasma and urine, and reduced risk of breast cancer [28,36].…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, Asian women have a three-fold lower breast cancer risk than women in the United States, independent of body weight [33]. However, second and third generation descendants of women who migrated from Asia to Western countries have breast cancer risks similar to those of women in the host country, suggesting that lifestyle and dietary habits, and not genetic factors explain the low breast cancer risk of women in Asia [30,34,35]. Furthermore, epidemiologic studies have detected an association between phytoestrogen consumption, phytoestrogen levels in plasma and urine, and reduced risk of breast cancer [28,36].…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to explain the international differences in breast cancer incidence rates, a number of investigators have compared hormone levels in healthy Asian and Caucasian women, with most focusing on differences in oestrogen levels (MacMahon et al, 1974;Moore et al, 1983;Trichopoulos et al, 1984;Goldin et al, 1986;Goodman et al, 1988;Bernstein et al, 1990;Shimizu et al, 1990;Key et al, 1990;Probst-Hensch et al, 2000) and a few examining androgens or androgen precursors (Bulbrook et al, 1967;Wang et al, 1976;Hayward et al, 1978). However, these studies could not distinguish the role of genetic differences from the effects of an Asian lifestyle on endogenous hormone levels.…”
Section: Discussionmentioning
confidence: 99%
“…These include findings from controls participating in a population-based case-control study of breast cancer in the US and China , and hormone comparisons between JapaneseAmericans and US Caucasians participating in the Multiethnic Cohort (Probst-Hensch et al, 2000). These studies showed oestrogens were higher in Caucasians than Asian women living in China, but similar to, if not slightly lower than levels in Japanese-Americans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations